Blockade of interleukin-33 activities by recombinant interleukin-33 Trap Fc protein would be a novel therapeutic strategy in allergic asthma - Thanh Nguyen, Thao Thi; Hong Vo, Phuc; Dang Nguyen, Quan (Vietnam Journal of Biotechnology, 2022)
The majority of autoimmune and allergic diseases are associated with abnormal expression of interleukin (IL)-33, a member of the IL-1 family of cytokines, that function dually as a proinflammatory cytokine and a transcriptional factor. We created an IL-33 inhibitor called "IL-33 Trap Fc" constructed by fusion of an Fc fragment of human immunoglobulin G1 and two distinct extracellular part receptors involved in interacting with IL-33, IL-1 receptors accessory protein, and IL-33 receptor. IL-33 Trap Fc was expressed by two systems, mammalian HEK293 cells and Pichia pastoris yeast. We found that these recombinant proteins were expressed as a glycoprotein and perhaps in dimeric form. IL-33 Trap Fc from HEK293 and P. pastoris suppressed the activity of IL-33 in vitro culture conditions. The glycosylation of IL-33 Trap expressed by P. pastoris yeast was more intensive and heterogeneous than the counterpart protein expressed from HEK293 cells. That is maybe one reason leading to a substantial decrease in the activity of IL-33 Trap Fc from P. pastoris compared with that from HEK293 cells. We also demonstrated that IL-33 Trap Fc expressed from HEK293 cells had therapeutic effects in ovalbumin-induced asthma mouse model. These data collectively suggested that IL-33 Trap Fc potently blocks IL-33 in vitro and in vivo, which may be a novel therapeutic strategy for IL-33-mediated allergic diseases.